Computational methods in analysis of gene regulation and protein interactions - Shamir, Ron (Henry Stewart Talks, 2012)
Finding regulatory motifs, Finding motifs using target sets of promoters, Problem definition, The Amadeus motif finding algorithm, Architecture, benchmark results and global analysis, Finding transcriptional programs and their regulatory motifs, Problem definition, The Allegro software for recovering transcriptional program, Results on yeast osmotic shock expression profiles, Recovering microRNA binding motifs from 3' UTRs using stem cell expression profiles, Discovering a novel motif pair in C. elegans, Utilizing network information, Using expression and protein interaction data, Problem definition and the Matisse algorithm, Demonstration of Matisse on yeast osmotic shock data, Comparison of Matisse to other algorithms, Demonstration of Matisse on human stem cell data, The pluripotency network, Using expression and protein interaction data with interaction confidence, The Cezanne algorithm, DNA damage response in yeast
Reviewed at 2020/10/19